Está en la página 1de 8

n

R
a = (a1, ..., an)
f(a1, ..., ai - 1, ai + h, ai + 1, an) - f(a1, ..., an)
lim
h 0 h

f(a)
xi

f(x1, ..., xn)


f(x1, x2, ..., xn)
xi

fx (x1, x2, ..., xn)


i

d
f(1, 0)
dy

2 2 3 2
f(x, y, z ) = x y - y z + x z
2
f=2xy+z
x
2 3
f=x -2yz
y
2 2
f = -3 y z + 2 x z
z
f(x, y) = cos(x y) + sen(y)
fy

f = -x sin(x y) + cos(y)
y

f(1, )
y

2 2 3 2
f(x, y, z ) = x y - y z + x z

2
2xy+z

R2 x0, y0

f f x0, y0
x y

f(x, y) - f(x0, y0) - f(x0, y0) (x - x0) - f(x0, y0) (y - y0)
x y

x0, y0
2 2
(x - x0) + (y - y0)

fx fy

x0, y0 x0, y0
2
R

d
f(0, 0) = 0
dx
d
f(0, 0) = 0
dy

f(x, y) := x cos(y) + x 2 y + y 2
2
f(x, y) = cos(y) + 2 x y f(x, y) = -x sin(y) + x + 2 y
x y
fx fy fxy fyx
x0, y0 x0, y0
fxy(x0, y0) = fyx(x0, y0)

fxyy

2y

-sin(y) + 2 x

-x cos(y) + 2

-sin(y) + 2 x

-cos(y)
dw dw dx
=
dt dx dt

2 2
x +y h(z ) = z

2 2 2
x +y x(t) = t y(t) = t

dz 1 1 2 3
=2x + (2 y)(2 t) 2 t +2t 2t=1+4t
dt 2 2 t

dz 1 + 4 t 3
=
dt
z = r2 + s2 r = x-y s=x+y zx zy


z= z r + z s
x r x s x


z= z r + z s
y r y s y

zx = 4 x zy = 4 y

3 3 2
f(x, y) = x + y - 3 x y
x
f(x, y) = x y +
y
4 4
f(x, y) = x - y

y
u(x, y) = arctan
x

2 2 t
z= x +y x = e y = sin(t) z
t

f(x, y) = x 2 + y
(x y)
f(x, y) = e

f(x, y) = 2 + x + y